2019
DOI: 10.5114/pjp.2019.93132
|View full text |Cite
|
Sign up to set email alerts
|

Green tea extract prevents the development of nonalcoholic liver steatosis in rats fed a high-fat diet

Abstract: Green tea contains many polyphenolic constitutes, which might prevent non-alcoholic fatty liver disease (NAFLD). We aimed to investigate whether green tea extract (GTE) given at doses reflecting habitual consumption of green tea beverages prevents development of NAFLD in rats fed a high-fat diet (HFD). Twenty-four male Wistar rats were randomly divided into four equal groups (two study and two control groups). The study groups received a HFD (approximately 50% energy from fat), enriched with 1.1% and 2.0% GTE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Selenium-Enriched Chaoqing Green Tea (GT8). The results were consistent with previous studies (16,17,20).…”
Section: Histopathological Evaluation Of Liversupporting
confidence: 94%
See 1 more Smart Citation
“…Selenium-Enriched Chaoqing Green Tea (GT8). The results were consistent with previous studies (16,17,20).…”
Section: Histopathological Evaluation Of Liversupporting
confidence: 94%
“…Green tea extract has been used to treat antiobesity (11). On the other hand, growing studies showed the effect of green tea on the prevention and management of NAFLD (16)(17)(18). The hepatoprotective and antiobesity effects of green tea are mainly attributed to its rich bioactive compounds, such as polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively high doses of GTE, which did not reflect the amounts of green tea consumed by humans through diet, was used in these animal studies. Karolczak et al (2019) found that GTE supplementation reflecting habitual consumption of 5 -8 cups of this beverage per day successfully reduced the amount of hepatic fat in rats fed with HFD. In the present work, we used tea drink, a common method of tea consumption, to investigate the action of green tea on HFD-induced NAFLD.…”
Section: Discussionmentioning
confidence: 88%
“…46 Karolczak et al studied whether GTE at a dose of habitual green tea beverages could prevent NAFLD in high-fat diet (HFD) rats, indicating the hepatoprotective potential of GTE in preventing dietinduced hepatic steatosis. 47 Heukcha (HCE) is a natural postfermentation green tea extract, which can inhibit high cholesterol diet-induced liver oxidative stress, lipid accumulation and fibrosis, and suppress hypercholesterolemia by increasing the expression of CYP7A1 disease and the occurrence of NAFLD. 48 Ninghong black tea extract could alleviate HFD-induced NAFLD by promoting the expression of peroxisome proliferator-activated receptor α (PPARα) and microsomal triglyceride transfer protein (MTP) in liver tissue, thereby promoting fatty acid β-oxidation and very low-density lipoprotein synthesis.…”
Section: Intervention Of Nafld Through Tea Drinkingmentioning
confidence: 99%
“…Hussain et al investigated the effects of green tea extract (GTE) supplementation in NAFLD patients and showed that a GTE diet could improve metabolic, chemical, inflammatory, and radiological parameters in nondiabetic and dyslipidemic NAFLD patients . Karolczak et al studied whether GTE at a dose of habitual green tea beverages could prevent NAFLD in high-fat diet (HFD) rats, indicating the hepatoprotective potential of GTE in preventing diet-induced hepatic steatosis . Heukcha (HCE) is a natural postfermentation green tea extract, which can inhibit high cholesterol diet-induced liver oxidative stress, lipid accumulation and fibrosis, and suppress hypercholesterolemia by increasing the expression of CYP7A1 disease and the occurrence of NAFLD .…”
Section: Prevention Intervention and Treatment Strategies For Nafldmentioning
confidence: 99%